Cloning and expression of antibody fragment (Fab) I: effect of expression construct and induction strategies on light and heavy chain gene expression - Mehta, Deepa; Chirmade, Tejas; Tungekar, Aatir A.; Gani, Kayanat; Bhambure, Rahul (Biochemical Engineering Journal, 2021)
Dual promoter expression constructs offer time and cost-effective alternatives to produce multi-domain proteins like antibody fragments. This investigation is focused on understanding the effect of expression construct (dual promoter vs. co-transformation strategy), codon optimization, and induction strategies on yield and expression stoichiometry of LC and HC genes of antibody fragment at shake-flask and bioreactor scale. rHu biosimilar Ranibizumab was selected as a model protein for the study. Expression stoichiometry of HC and LC gene at mRNA level was studied using RTqPCR, whereas protein expression level was studied quantitatively using RP-HPLC and SDS-PAGE analysis. In the case of dual promoter expression construct, it was observed that LC gene cloned in the MCS1 of the duet vectors has > 2-fold expression than the HC gene, cloned in the MCS2. Transcript abundance profile of the HC and LC genes determined at different time intervals post-induction shows a difference in the gene expression at the transcriptional level. Comparative analysis of dual promoter and co-transformation strategy shows better stoichiometry in co-transformation (1:1.3), whereas higher protein yield in a dual expression system (>2.4 fold). The use of lactose and galactose as inducers show higher Fab yield of 2.30 +/- 0.03 g/L and 2.81 +/- 0.06 g/L with expression stoichiometry of 1:1.9 and 1:2 (HC: LC) respectively than IPTG-based induction with a protein yield of 1.40 +/- 0.02 g/L.
Keywords: Dual promoter vector; Expression stoichiometry; High cell density fermentation; rHu biosimilar Ranibizumab; Transcript abundance